Hubungan Tingkat Pengetahuan Akseptor Keluarga Berencana dan Peran Tenaga Kesehatan dengan Minat Penggunaan Kontrasepsi Jangka Panjang (MKJP) - Maria T. E. Koba; Frans G. Mado; Yoseph Kenjam (Universitas Nusa Cendana, 2019)
Family planning aims at reducing maternal mortality rates and reducing population growth rate with the main target of couples of childbearing age. One of the family planning options offered is long-term reversible contraceptive method (MKJP). The purpose of this study was to determine the factors associated with interest in using MKJP in the work area of Camplong health center, Fatuleu sub-district, Kupang regency in 2018. The research was quantitive study with cross-sectional approach. The sample of 77 people was selected using simple random sampling. The instrument uses was a questionnaire. Data analysis techniques consisted of descriptive and bivariate analysis (chi-square test) with α= 0,05. The study indicated that knowledge (p-value= 0,09) and the role of health workers (p-value =0,001) were associated with the use of the MKJP while attitude (p-value = 0,765) and husband support (p-value = 0,131) had no relationship with MKJP. Health center needs to regularly provide information to the community about the advantages of MKJP especially for couples of childbearing age who have already had more than three children.